Effect of Ethanol Concentration and Extraction Time on Piperine Yield from Piper retrofractum Vahl. - Gema Fitriyano; Rudi Septian Herfindo; Erna Kurnia Wati (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), 2026)
Piperine, the primary bioactive compound in Piper retrofractum Vahl or Javanese long pepper, offers various pharmacological benefits, including anti-inflammatory, anticancer properties, and the enhancement of drug bioavailability. The need for efficient piperine extraction has grown as ongoing research emphasizes its potential as a key component in the pharmaceutical and nutraceutical industries. This study aims to evaluate the impact of ethanol concentration and maceration time on the yield of piperine from the plant Piper retrofractum Vahl, commonly known as Javanese long pepper. Piperine is the primary active compound responsible for the pharmacological properties and the pungent taste characteristic of the plant. An ethanol-based extraction method was chosen due to its perceived environmental friendliness and cost-effectiveness. In this study, extraction was carried out using various ethanol concentrations (75%, 80%, 85%, 90%, and 95%) and different maceration durations (14, 16, 18, 20 and 22 hours). The results showed that increasing ethanol concentration and extending maceration time significantly enhanced the piperine yield, with the optimal piperine concentration obtained using 95% ethanol and a maceration time of 20 hours. The extraction product from this operating condition yielded about 35.02%, with a piperine content of 3.245%.